Metal–organic frameworks based on a benzimidazole flexible tetracarboxylic acid: Selective luminescence sensing Fe3+, magnetic behaviors, DFT calculations, and Hirshfeld surface analyses. (5th September 2021) - Zhang, Xiaoyu; Xiong, Dingqi; Fu, Pengkun; Yun, Meng; Yang, Qinglin; Jia, Mei‐Mei; Dong, Xiuyan
Abstract: Four novel metal–organic frameworks constructed from benzimidazole flexible tetracarboxylic acid ligand, 1‐(3, 5‐dicarboxylbenzyl)‐1H‐benzimidazole‐5, 6‐dicarboxylic acid (H4 L), have been prepared by a solvothermal method in the presence of N‐donor ancillary ligands (1, 10‐phen = 1, 10‐phenanthroline monohydrate, 4, 4′‐bibp = 1, 4‐di[pyridine‐4‐yl]benzene), namely, [Co2 (L)(H2 O)3 ]n (1), {[Cd2 (L)(1, 10‐phen)(H2 O)]·2H2 O}n (2), {[Co4 (L)2 (4, 4′‐bibp)2 (H2 O)7 ]·4H2 O}n (3), and {[Ni4 (L)2 (4, 4′‐bibp)2 (H2 O)7 ]·4H2 O}n (4) . Complexes 1 and 2 show a 3D supramolecular structure and crystallize in monoclinic space group P 21 /c . Complexes 3 and 4 are isomorphous and crystallize in monoclinic space group P n, and the respective metals exhibit a similar coordination environment. The H4 L ligand behaved in different coordinated modes in Complexes 1–4, namely, μ6 ‐η 1 :η 1 :η 1 :η 0 :η 1 :η 1 :η 1 :η 1 :η 1 in 1, μ6 ‐η 1 :η 1 :η 1 :η 1 :η 1 :η 1 :η 2 :η 1 :η 1 in 2, there are two coordination modes (μ5 ‐η 0 :η 1 :η 1 :η 0 :η 1 :η 1 :η 1 :η 0 :η 1 and μ5 ‐η 1 :η 1 :η 1 :η 0 :η 1 :η 1 :η 1 :η 0 :η 1 ) in 3 and 4 . Furthermore, photoluminescence and magnetic properties have been studied. The results indicate that Complexes 3 and 4 show strong antiferromagnetic and ferromagnetic coupling through M–O–C–O–M interactions, respectively. In particular, Complex 2 can sensitively and selectively detect Fe 3+ in aqueous systems, and the limit of detection (LOD) values of Fe 3+ is ∼0.19 mM. Abstract : Four novel transition metal MOFs (1–4 ) have been successfully synthesized with the mixed‐ligand strategy based on a predesigned functional flexible benzimidazole tetracarboxylic acid ligand (H4 L) and different N‐donor ancillary ligands. Of these, Complex 2 can sensitively and selectively detect Fe 3+ in aqueous systems, and the possible sensing mechanism has been investigated using UV–vis spectroscopy, and Complexes 3 and 4 show strong antiferromagnetic and ferromagnetic coupling through M–O–C–O–M (Co for 3, Ni for 4) interactions, respectively.